Progress and industrialization development trends of the anaerobic digestion technologies for bio-natural gas - Zhu, Hongguang; Lu, Fulu; Pan, Fanghui (International Journal of Agricultural and Biological Engineering, 2024)
The production of bio-natural gas through anaerobic digestion not only realize the resource utilization and harmless treatment of urban and rural organic wastes, but also reduce the emission of methane and carbon dioxide. However, as an independently industry, bio-natural gas has some prominent challenges compared to household biogas and small-scale biogas projects. For the healthy development of the bio-natural gas industry, system analysis and planning have become particularly important. This study reviews the current development status of the bio-natural gas industry and innovatively analyzes the development direction of industry from a multidimensional perspective. Leading opinions are provided based on system analysis. Three major technological breakthroughs that have supported the success of regional bio-natural gas industry are revealed. The completeness of industrial technology, the objectivity of industrial regional development and the inevitability of the comprehensive benefits of the industrial chain are the major development direction of the bio-natural gas. Finally, according to the three major demands of new energy fuel, electricity and energy storage, two new energy systems based on bio-natural gas and the synergistic development of multiple new energy sources are proposed. This study provides theoretical and practical guidance for the bio-natural gas industry. Key words: bio-natural gas; anaerobic digestion; technological progress; industrialization; sustainable developmentDOI: 10.25165/j.ijabe.20241704.9036Citation: Zhu H G, Lu F L, Pan F H. Progress and industrialization development trends of the anaerobic digestion technologies for bio-natural gas. Int J Agric & Biol Eng, 2024; 17(4): 1–12.